1989
DOI: 10.1084/jem.170.3.959
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of inflammation, tissue damage, and mortality in bacterial meningitis in rabbits treated with monoclonal antibodies against adhesion-promoting receptors of leukocytes.

Abstract: We tested if specific inhibition of recruitment of leukocytes across the blood brain barrier from the vascular compartment to the cerebrospinal fluid (CSF) space reduced tissue damage and improved the outcome of infection in a rabbit model of experimental meningitis. The CD11/CD18 complex of receptors on leukocytes promotes adhesion of these cells to endothelia, a process required for egress of cells into the extravascular space. Intravenous injection of the anti-CD18 mAb IB4 effectively blocked the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
142
2
4

Year Published

1991
1991
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(159 citation statements)
references
References 35 publications
10
142
2
4
Order By: Relevance
“…Although neutrophils are critically important to fight against bacterial sepsis, depletion of peripheral neutrophils in a murine hematogenous model of GBS meningitis prolonged survival, decreased bacterial CNS load, and decreased BBB leakage in GBS-infected mice (Banerjee et al 2011). Correspondingly, prevention of leukocyte infiltration into the CNS using anti-CD18 antibody has been shown to improve pneumococcal and HiB meningitis outcomes (Tuomanen et al 1989;Saez-Llorens et al 1991).…”
Section: Inflammation and Bbb Permeabilitymentioning
confidence: 99%
“…Although neutrophils are critically important to fight against bacterial sepsis, depletion of peripheral neutrophils in a murine hematogenous model of GBS meningitis prolonged survival, decreased bacterial CNS load, and decreased BBB leakage in GBS-infected mice (Banerjee et al 2011). Correspondingly, prevention of leukocyte infiltration into the CNS using anti-CD18 antibody has been shown to improve pneumococcal and HiB meningitis outcomes (Tuomanen et al 1989;Saez-Llorens et al 1991).…”
Section: Inflammation and Bbb Permeabilitymentioning
confidence: 99%
“…More recently, it was shown that S. pneumoniae may also be recognized by inflammasomes that are dependent upon the adaptor molecule ASC (16)(17)(18)(19). Together, these pathways initiate immune activation and lead to production of inflammatory cytokines and chemokines that subsequently mediate the recruitment of leukocytes to the site of infection (20)(21)(22)(23)(24)(25)(26). However, when this occurs within the brain, the ensuing inflammatory response is argued to ultimately cause neuronal damage and/ or death (9,10).…”
mentioning
confidence: 99%
“…TLR activation results in MyD88-dependent production of high levels of cytokines and chemokines (6), which facilitates the accumulation of large amounts of blood-borne leukocytes (predominantly neutrophils) inside the CSF. The resultant excessive neutrophilic inflammation causes collateral damage to the brain, thus contributing substantially to the unfavorable outcome of meningitis (7,8).…”
mentioning
confidence: 99%